Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acsaem.2c01174
|View full text |Cite
|
Sign up to set email alerts
|

Atomically Dispersed CuNx Sites from Thermal Activation of Boron Imidazolate Cages for Electrocatalytic Methane Generation

Abstract: Atomically dispersed metal sites (ADMSs) have been recognized as promising candidates for electrochemical conversion. Among a diverse range of molecular precursors for ADMS synthesis, framework materials are particularly interesting due to their high degree of tunability and control over the primary coordination sphere of the metal ions. Herein, we demonstrate that a copper boron imidazolate cage, BIF-29­(Cu), is a convenient precursor for a competent catalyst with isolated Cu sites coordinated by N donors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 70 publications
(125 reference statements)
0
7
0
Order By: Relevance
“…In comparison to the recently published electromethanation of CO 2 (Figure a), Cu–DCD 40 demonstrates high selectivity (FE) and activity (partial current density) of electromethanation. , To evaluate the stability of the as-prepared catalyst, “pause electrolysis” to suppress the carbonate issue is adopted in this work . The pause electrolysis is shown in Figure b.…”
Section: Resultsmentioning
confidence: 98%
“…In comparison to the recently published electromethanation of CO 2 (Figure a), Cu–DCD 40 demonstrates high selectivity (FE) and activity (partial current density) of electromethanation. , To evaluate the stability of the as-prepared catalyst, “pause electrolysis” to suppress the carbonate issue is adopted in this work . The pause electrolysis is shown in Figure b.…”
Section: Resultsmentioning
confidence: 98%
“…Infrared absorption spectroscopy (FTIR), Figure D, red trace) showed characteristic B–H (2426 cm –1 ), imidazole C–H (3132 cm –1 ), and axial water O–H (3435 cm –1 ) bands. Previous reports have illustrated the feasibility of dissolving the resulting framework material into colloidally stable solutions by disrupting the van der Waals interactions between cages. , This unique feature of the framework material lends itself to versatile processability and incorporation into electrochemical systems. The colloidal stability of a 1 mg mL –1 MeOH solution of BIF-29­(Cu) was confirmed by dynamic light scattering (DLS) measurements, which showed an average particle size of 300 nm (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Boron-imidazolate frameworks (BIFs) are a subset of MOFs that are composed of metal-imidazole-boron linkages. These materials are credited for having versatile structural topologies while also maintaining high chemical and thermal stability . Recently, our group has shown that BIF-29­(Cu), a copper-containing BIF, and its thermolyzed derivative produce methane from CO 2 RR with high selectivity (32 and 55%, respectively) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations